Efektivitas Penguraian Sampah Organik Pasar Menggunakan Larva Black Soldier Fly - Asri Triwandani; Pramiati Purwaningrum; Ratnaningsih Ruhiyat (Fakultas Teknik, 2023)
Organic waste dominates the waste sourced from the market so it needs to be processed before it goes to the TPA. Utilization of BSF larvae is an effort to process organic waste in reducing the volume of waste that will be disposed of in the TPA. The purpose of this study was to determine the ability of BSF larvae to reduce organic waste on the market. The composition of the type of waste used consisted of fruit, vegetable, food waste and mixtures (50% fruit waste: 40% vegetable waste: 10% food waste waste) with a variation of feeding rate of 40, 60 and 80 mg/larvae/day. The number of larvae included in each reactor was 4000 individuals (70 grams) using 5-day larvae (5-DOL) with a composting duration of 18 days. The results showed that BSF larvae were able to reduce organic waste under optimum pH conditions ranging from 7.5- 8.3 with an average temperature of around 31⁰C and humidity ranging from 56-88%. The reduction results obtained in this study were 78% for various vegetables with a feeding rate of 60 mg/larvae/day. The best results of laboratory analysis based on SNI 19-7030-2004 are mixed sample variations with a feeding rate of 80 mg/larvae/day which have a C-Organic content of 32.55%, a C/N ratio of 17%, a moisture content of 12.89%, N total 1.88%, P2O5 2.22% and K2O 2.68%.